PENGEMBANGAN "CERPEN SAKU" SEBAGAI WAHANA BELAJAR BERBASIS WEB PADA MATERI TEKS SASTRA DI SEKOLAH MENENGAH PERTAMA - Fadhila, Alfi; Rakhmawati, Ani (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2024)
The importance of the Indonesian language is the basis for the enactment of the policy that Indonesian must be applied and learned as a subject at all levels of education. Text-based Indonesian learning is a form of learning that is proclaimed in the Education curriculum in Indonesia. The era of development 4.0 provided many developments in the fields of technology and information, which also spread to the field of education. In the application of technology and information in the field of education, it is appropriate for education in Indonesia to use technology as a supporting element of the learning process. In fact, the implementation of learning in schools is still experiencing problems regarding the media used. The lack of learning media innovation in existing learning is the basis for the need to develop web-based visual media as a supporting facility. The research methodology is based on a five-step research and development approach that includes identifying opportunities and problems, data collection, product design, design validation, and design review. This study only uses stages one to three. The resulting product design is in the form of a learning website called "Pocket Short Stories," which contains material on short stories, student short story works, as well as dictionary references. The development of Pocket Short Stories aims to create fun and flexible text-based learning in Indonesian. Short stories have three features: 1) Get to know Short Stories; 2) My short story; and 3) Diction House.Keywords: Indonesian, Learning Media, Short Story Text.  AbstrakPentingya Bahasa Indonesia menjadi dasar diberlakukannya kebijakan bahwa Bahasa Indonesia wajib diterapkan dan dipelajari sebagai pelajaran di semua jenjang pendidikan. Pembelajaran Bahasa Indonesia berbasis teks merupakan bentuk pembelajaran yang dicanangkan pada kurikulum Pendidikan di Indonesia. Era perkembangan 4.0 memberikan banyak perkembangan dalam bidang teknologi dan informasi yang juga menjalar dalam bidang pendidikan. Dalam penerapan teknologi dan informasi di bidang pendidikan, sudah sepatutnya pendidikan di Indonesia menggunakan teknologi sebagai unsur pendukung proses pembelajaran. Pada kenyataannya, pelaksanaan pembelajaran di sekolah masih mengalami kendala perihal media yang digunakan. Minimnya inovasi media belajar pada pembelajaran yang ada menjadi dasar perlunya pengembangan media visual berbasis web sebagai sarana penunjang. Metodologi penelitian didasarkan pada pendekatan penelitian dan pengembangan menggunakan lima langkah yang mencakup mengetahui peluang dan masalah, pengumpulan data, desain produk, validasi desain, dan tinjauan desain. Pada penelitian ini hanya menggunakan tahap satu sampai tiga.   Desain   produk   yang dihasilkan berupa website belajar bernama "Cerpen Saku" yang berisi materi tentang cerita pendek, karya-karya cerpen siswa, serta referensi diksi. Pengembangan Cerpen Saku bertujuan untuk mewujudkan pembelajaran Bahasa Indonesia berbasis teks yang menyenangkan dan fleksibel. Cerpen Saku memiliki tiga fitur: 1) Kenal Cerpen; 2) Cerpenku; dan 3) Rumah Diksi.Kata Kunci: Bahasa Indonesia, Media Pembelajaran, Teks Cerpen.